2006
DOI: 10.1111/j.1439-0450.2006.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Acute Phase Protein Concentrations in Different Diseases in Field Conditions

Abstract: Five acute phase proteins (APPs) [C-reactive protein (CRP), serum amyloid A (SAA), haptoglobin (Hp), pig-MAP and albumin] were measured in pigs with naturally occurring infections by porcine reproductive and respiratory syndrome virus (PRRSV), Aujeszky's disease virus (ADV), porcine circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae, and in animals with tail and ear bites, arthritis and other acute inflammatory processes. Healthy specific pathogen-free (SPF) pigs were used as controls. In PRRSV-infected pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 29 publications
7
73
2
2
Order By: Relevance
“…This result agrees with those obtained in pigs clinically affected after experimental infection with Aujeszky virus and Aujeszky field cases, where a more sensitive response of haptoglobin changes is observed compared to Pig-MAP (Parra et al, 2006;Carpintero et al, 2007), although, in our case, the magnitude of the increase is lower than the described for these authors. These results are foreseeable because the virulence of a MLV is always lower than the wild virus (Shams, 2005).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This result agrees with those obtained in pigs clinically affected after experimental infection with Aujeszky virus and Aujeszky field cases, where a more sensitive response of haptoglobin changes is observed compared to Pig-MAP (Parra et al, 2006;Carpintero et al, 2007), although, in our case, the magnitude of the increase is lower than the described for these authors. These results are foreseeable because the virulence of a MLV is always lower than the wild virus (Shams, 2005).…”
Section: Discussioncontrasting
confidence: 44%
“…-E-mail: anna.bassols@uab.cat post-weaning multisystemic wasting syndrome and porcine respiratory disease complex (Segales et al, 2004;Parra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our definition of health status is based on the presence of major swine diseases that consistently affect both animal welfare and performance (Poppe et al, 1998;Pallarés et al, 2000;Regula et al, 2000;Segalé s et al, 2004), although the use of APP as potential indicators of health status is currently under investigation (Parra et al, 2006;Tecles et al, 2007). In general, the traits we measured were consistent between high and lower health status farms, with two notable exceptions, levels of WBC and CD8a 1 cells.…”
Section: Discussionmentioning
confidence: 75%
“…Acutephase proteins are suggested to be useful markers for the monitoring of some diseases, and Hp is the most sensitive acute-phase protein to detect pathological states in pigs [18]. In the present study SAA was found to be a good indicator in pigs acutely exposed to DON.…”
Section: Vivomentioning
confidence: 57%